2015
DOI: 10.1007/s00417-015-3012-4
|View full text |Cite
|
Sign up to set email alerts
|

In-vivo mapping of drusen by fundus autofluorescence and spectral-domain optical coherence tomography imaging

Abstract: The appearance of soft drusen on CFP does not allow for differentiation between preserved and markedly compromised outer retinal integrity, including incipient atrophy and focal neurosensory alterations of reflectivity overlying extracellular sub-retinal pigment epithelium (RPE) deposits. Multimodal imaging reveals a broad spectrum of microstructural changes, which may reflect different stages in the evolution of drusen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…For in vivo en face imaging, Delori et al 29 found hypoautofluorescence of the drusen center, often surrounded by a hyperfluorescent annulus. Göbel et al 30 found drusen with increased, decreased, as well as unremarkable autofluorescence intensity. In a recent clinical study, we found one-third of soft drusen to be hyperfluorescent.…”
Section: Discussionmentioning
confidence: 97%
“…For in vivo en face imaging, Delori et al 29 found hypoautofluorescence of the drusen center, often surrounded by a hyperfluorescent annulus. Göbel et al 30 found drusen with increased, decreased, as well as unremarkable autofluorescence intensity. In a recent clinical study, we found one-third of soft drusen to be hyperfluorescent.…”
Section: Discussionmentioning
confidence: 97%
“…Whereas Delori et al found hypo-fluorescence of the drusen center, often surrounded by a hyper-fluorescent annulus, 39 Göbel et al found drusen with increased, decreased, as well as unremarkable autofluorescence intensity. 40 Investigating refractile drusen, Suzuki et al found a transition from uniform hyper-FAF to a ring of hyper-FAF, presumably due to a phase of photoreceptor shortening followed by loss of the RPE on the top of the druse. 41 Accordingly, FLIO has revealed a wide variety in drusen fluorescence lifetimes.…”
Section: Discussionmentioning
confidence: 99%
“…Delori et al [64] noted variable FAF patterns over hard and soft drusen, but with hyper-AF surrounding drusen, suggesting changes in RPE metabolism. Focal vitelliform deposition over drusen may increase FAF signal, [65] but otherwise the intrinsic FAF signal from drusen is variable and cannot be used clinically to differentiate drusen types reliably. [9] Reticular pseudodrusen, or subretinal drusenoid deposits (SDD), represent an independent risk factor for progression to advanced AMD.…”
Section: Age-related Macular Degeneration (Amd)mentioning
confidence: 99%